2020
DOI: 10.3390/nu12092718
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Lactation and Maternal Risk of Metabolic Syndrome: A Systematic Review and Meta-Analysis

Abstract: Cardiovascular disease (CVD) is the leading cause of death of women across all ages, and targeting modifiable risk factors, such as those comprised in metabolic syndrome (MetS) (e.g., waist circumference, lipid profile, blood pressure, and blood glucose), is of great importance. An inverse association between lactation and CVD has been suggested, and lactation may decrease the risk of MetS. This systematic review and meta-analysis examined how lactation may affect the development and prevalence of MetS in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…breastfeeding a child) for mothers, although previous studies have suggested that lifetime duration of lactation is associated with a reduced risk of breast and thyroid cancer, metabolic syndrome, atherosclerosis and hypertension. [5][6][7][8][9] However, evidence of the effects of lactation on women's risk of developing type 2 diabetes is conflicting, with some studies suggesting a protective effect, whilst others report no association. [10][11][12][13][14] Almost all studies are limited by their inability to account for metabolic risk profiles before lactation, and previous history of gestational diabetes (GD), a strong risk factor for type 2 diabetes in women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…breastfeeding a child) for mothers, although previous studies have suggested that lifetime duration of lactation is associated with a reduced risk of breast and thyroid cancer, metabolic syndrome, atherosclerosis and hypertension. [5][6][7][8][9] However, evidence of the effects of lactation on women's risk of developing type 2 diabetes is conflicting, with some studies suggesting a protective effect, whilst others report no association. [10][11][12][13][14] Almost all studies are limited by their inability to account for metabolic risk profiles before lactation, and previous history of gestational diabetes (GD), a strong risk factor for type 2 diabetes in women.…”
Section: Introductionmentioning
confidence: 99%
“…Comparably less attention has been given to the benefits of lactation (i.e. breastfeeding a child) for mothers, although previous studies have suggested that lifetime duration of lactation is associated with a reduced risk of breast and thyroid cancer, metabolic syndrome, atherosclerosis and hypertension 5–9 . However, evidence of the effects of lactation on women's risk of developing type 2 diabetes is conflicting, with some studies suggesting a protective effect, whilst others report no association 10–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Women’s history of breastfeeding has been associated with lower risk of type-2 diabetes [ 18 ], hypertension, hyperlipidemia, cardiovascular disease [ 19 ], metabolic syndrome [ 20 ], myocardial infarction [ 21 ] and breast cancer [ 22 ], as well as AD [ 23 ]. Type-2 diabetes [ 24 ], hypertension [ 25 ], hyperlipidemia and cardiovascular disease [ 26 ] have each been associated with enhanced risk of AD in multiple studies with a few exceptions [ 28 ], with these epidemiological patterns likely due to compromise of brain metabolism and cerebrovascular function [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason might be that many people worldwide do not meet their dairy requirements, especially in the developing countries [56,57], and lack physical activity [54]. The results from this meta-analysis with recent evidence on T2DM [5], all-cause mortality [6,7], and specific cancer risks [8,9] provide further support for public health advice on increasing the consumption of dairy products [58], fruits/vegetables [59], and increasing physical activity [54], limiting the risk of MetS, its components, and CVD, especially CAD, in the global population.…”
Section: Discussionmentioning
confidence: 57%
“…MetS and its five individual components affect the blood vessels. As a result it is associated with extending the risk of cardiovascular disease by two-fold (CVD), type 2 diabetes mellitus (T2DM ) by five-fold [5], and all-cause mortality by 1.5 fold [6,7], along with elevating some specific cancer risks [8,9]. In recent years, the ubiquity and frequency of MetS have quickly progressed globally [10].…”
Section: Introductionmentioning
confidence: 99%